A validated method for the rapid quantification of melatonin in over-the-counter hypnotics by the atmospheric pressure solid analysis probe (ASAP). Issue 16 (6th April 2022) - Moser, Daniel; Hussain, Shah; Rainer, Matthias; Jakschitz, Thomas; Bonn, Günther K.
Abstract : Melatonin is a hormone that regulates the biological day and night cycle. Abstract : Melatonin is a hormone that regulates the biological day and night cycle. It is mainly produced by the pineal gland during the night. People suffering from insomnia use it as a soporific drug. The aim of this study was to develop a method for the rapid quantification of melatonin in hypnotics. For that purpose, atmospheric pressure solid analysis probe-assisted mass spectrometry was applied, where no chromatographic separation is needed. Thereby, one single analysis takes less than 1 min. Reference measurements were performed with ultra-high-performance liquid chromatography coupled with a quadrupole-time-of-flight mass spectrometer. Both methods were validated and real sample extracts were tested. The coefficients of determination were above 0.97 for both methods. The limits of detection and quantification were below 1 mg kg −1 . Both methods gave comparable results. Moreover, the content of melatonin differed from the specified value in many samples. The highest and lowest observed deviations were 78% and 1%, respectively.